Penerapan Metode Trend Moment Untuk Memprediksi Jumlah Pertumbuhan Penduduk - Amalia, Laily Rizky; Ramdhan, William; Kifti, Wan Mariatul (Building of Informatics, Technology and Science (BITS), 2022)
Population growth is caused by three components, namely birth (fertility), death (mortality), and migration. These three components greatly affect the process of population growth that occurs. The development of population growth in one sub-district is very important to be detailed so that the development of the subdistrict can be improved. Forecasting is an important tool in effective and efficient planning. An important step after forecasting is done is verification of forecasting in such a way that it reflects past data and the underlying causal systems of such growth. As long as the forecasting representation is reliable, forecasting results can continue to be used. The purpose of this study is to apply the Trend Moment method to predict the population growth in Joman Water District in the next few years based on three components, namely birth (fertility), death (mortality), and migration. The results of this study can predict the number of population growth using the Trend Moment Method in 2022 with birth rates of 1573, 641 arrivals, 601 arrivals, and 235 displacements with errors below 10%